2022
DOI: 10.1051/0004-6361/202141811
|View full text |Cite
|
Sign up to set email alerts
|

Organic chemistry in the protosolar analogue HOPS-108: Environment matters

Abstract: Context. Hot corinos are compact regions around solar-mass protostellar objects that are very rich in interstellar Complex Organic Molecules (iCOMs). How the abundance of these molecules is affected by the environmental physical conditions is still an open question. More specifically, addressing this point is key to understand our own chemical origins since the Solar System formed in a large cluster of low- to high-mass stars and was therefore subject to external heating and ultraviolet irradiation which may h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…Indeed, the CH 3 OCH 3 /HCOOCH 3 ratio in CB68 is 0.74 ± 0.11, which is almost comparable to those for the other sources. A trend of the constant CH 3 OCH 3 /HCOOCH 3 ratio is also reported by (Chahine et al 2022). On the other hand, the other ratios shows some variation from source to source.…”
Section: Comparison With Other Sourcessupporting
confidence: 59%
See 1 more Smart Citation
“…Indeed, the CH 3 OCH 3 /HCOOCH 3 ratio in CB68 is 0.74 ± 0.11, which is almost comparable to those for the other sources. A trend of the constant CH 3 OCH 3 /HCOOCH 3 ratio is also reported by (Chahine et al 2022). On the other hand, the other ratios shows some variation from source to source.…”
Section: Comparison With Other Sourcessupporting
confidence: 59%
“…CB 68 (L146) is a small, nearby, slightly comet-shaped opaque Bok globule located in the outskirts of the Ophiuchus molecular cloud complex (Nozawa et al 1991;Lemme et al 1996;Launhardt & Henning 1997;Launhardt et al 1998). The canonical distance to the Ophiuchus molecular cloud complex of 160 pc has been used historically (Chini 1981;Launhardt & Henning 1997;Launhardt et al 2010). However, Lombardi et al (2008) reported the distance to the Ophiuchus molecular cloud complex to be 119 ± 6 pc by using the Hipparcos and Tycho parallax measurements with the Two Micron All Sky Survey data.…”
Section: Introductionmentioning
confidence: 99%
“…SIMBA-a seems to have a lower methanol abundance than the other sources but since the LVG analysis has been performed with only a few data points for most of the sources, the accuracy of the fit is not very elevated. So far, only three hot corinos have been identified in the OMC-2/3 filament, the intermediate mass protostars HOPS-87 and HOPS-370 (Hsu et al 2020;Tobin et al 2019), and HOPS-108 (Tobin et al 2019;Chahine et al 2022). One of the questions we aim to answer is: how many hot corinos are present in the OMC-2/3 filament?…”
Section: Derivation Of Methanol Abundancesmentioning
confidence: 98%
“…On the other hand, we targeted 19 solar-mass protostars located in the OMC-2/3 filament and detected only five bona fide hot corinos. Even though three other hot corinos are located in the OMC-2/3 filament (HOPS-87, HOPS-370, HOPS-108; Tobin et al 2019;Hsu et al 2020;Chahine et al 2022) we do not take them into account. Indeed, unlike the above-cited studies, we performed a blind search for hot corinos using an observational setup completely analogous to that done in Perseus by Yang et al (2021).…”
Section: Are Oranges Different From Peaches?mentioning
confidence: 99%
See 1 more Smart Citation